FREQUENCY STABILITY ANALYSIS USING TIME DOMAIN SIMULATION METHOD (CASE STUDY OF TIMOR SYSTEM) - Seran, Dionisius Alfonso; Mauboy, Evtaleny R; Nursalim, Nursalim (Jurnal Media Elektro, 2024)
Based on the 2021-2030 RUPTL, the addition of PLTU Timor 1 (2 × 50 MW) to the Timor system is carried out because electricity demand continues to increase. Therefore, a transient stability study is needed, to determine the reliability of the system when a disturbance occurs. By utilizing the Time Domain Simulation (TDS) method, the research was conducted by simulating generator outage and 3 phase short circuit to study the frequency stability of the Timor system. From the simulation results, generator outage has a major influence on system frequency stability, especially simulated at PLTU Timor 1 unit 1. The disturbance caused a decrease in the lowest frequency reaching 49.61 Hz so that it was not within the safe operating limits according to the operating guidelines for the Timor electricity system. For this reason, Manual Load Shedding (MLS) and the addition of generators at PLTD Cogindo and PLTMG Kupang Peaker are required. The action is carried out by paying attention to the rate of change of the next frequency. As for the 3 phase short circuit disturbance on one of the Bolok - Maulafa lines, the frequency increased to 50.06 Hz after the disturbance which is still within safe operating limits.